2017
DOI: 10.3389/fimmu.2017.00796
|View full text |Cite
|
Sign up to set email alerts
|

Deconvolution of the Response to Bacillus Calmette–Guérin Reveals NF-κB-Induced Cytokines As Autocrine Mediators of Innate Immunity

Abstract: Bacillus Calmette–Guérin (BCG) is used as a vaccine and diagnostic test for tuberculosis, as well as immunotherapy in the treatment of bladder cancer. While clinically useful, the response to mycobacterial stimulation is complex and the induced protein signature remains poorly defined. We characterized the cell types directly engaged by BCG, as well as the induced cytokine loops that transmit signal(s) to bystander cells. Standardized whole-blood stimulations and mechanistic studies on single and purified cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…Interestingly, Dectin-1/2 responses were predominantly activated in neutrophils when compared with monocytes and lymphocytes populations. This work also demonstrated that induction of ROS production by BCG was decreased by neutralization of Dectin-1/2 and TLR-2/4 in both neutrophils and monocytes ( 47 ). In agreement with these findings, a recent report has shown that Mtb can induce DC maturation by generating ROS production through Dectin-1/TLR-2 ( 48 ).…”
Section: Dectin-1 Recognition Of Mycobacteriamentioning
confidence: 73%
See 1 more Smart Citation
“…Interestingly, Dectin-1/2 responses were predominantly activated in neutrophils when compared with monocytes and lymphocytes populations. This work also demonstrated that induction of ROS production by BCG was decreased by neutralization of Dectin-1/2 and TLR-2/4 in both neutrophils and monocytes ( 47 ). In agreement with these findings, a recent report has shown that Mtb can induce DC maturation by generating ROS production through Dectin-1/TLR-2 ( 48 ).…”
Section: Dectin-1 Recognition Of Mycobacteriamentioning
confidence: 73%
“…Interestingly, administration of Dectin-1 agonist, curdlan, together with a mycobacterial antigen TB10.4, induced Th1 and Th17 responses in neonatal mice infected with Mtb ( 45 ). A recent study by Bisiaux et al investigated cell-specific activation and pro-inflammatory responses in human whole blood stimulated with BCG ( 47 ). Interestingly, Dectin-1/2 responses were predominantly activated in neutrophils when compared with monocytes and lymphocytes populations.…”
Section: Dectin-1 Recognition Of Mycobacteriamentioning
confidence: 99%
“…activated neutrophils (18). In a recent study, Bisiaux et al (19) reported the secretion of TNF-α following BCG stimulation. il-1β is an important mediator of inflammatory response produced by activated macrophages, which is also involved in a variety of cellular activities, including cell proliferation, differentiation and apoptosis (20).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, CITRUS analysis also highlighted significantly lower frequencies of two TNF-expressing cell subsets in BCG compared to placebo recipients. One subset appeared to include a mixture of NK and NKT like cells that co-expressed IFNγ, while the other was negative for all lineage markers and may comprise monocytes or B cells, which have been shown to respond to BCG restimulation 71 . Confirmation of these subsets as BCG-responsive would require more detailed phenotyping.…”
Section: Discussionmentioning
confidence: 99%